Unusual modes of oogenesis and brooding in bivalves: the case of Gaimardia trapesina (Mollusca: Gaimardiidae) - Ituarte, Cristian Federico (Invertebrate Biology)
I describe an unusual case of follicular oogenesis in a bivalve, Gaimardia trapesina, a common marine bivalve from the Magellan Region and adjacent Sub-Antarctic waters, whose members brood their developing larvae. The gonad in G. trapesina is an acinus organ that infiltrates the perivisceral connective tissue; the walls of the acini are formed by tall, slender cells with distal nuclei, supported by a thin conjunctive tissue layer. At the onset of vitellogenesis, each developing oocyte becomes surrounded by a one-cell-thick layer of follicle cells, which may originate from the wall of the acinus. The cells form a follicle that completely encompasses single oocytes, except at the basal zone, where oocytes are in contact with the acinus wall. The follicle persists beyond the end of vitellogenesis and spawning. After gamete release, the persistent follicle participates in the attachment of ova and developing embryos to the interfilamental junctions of the inner and outer demibranchs of the gill, where embryos are incubated until hatching as late-stage pediveliger larvae. Ripe eggs are large (B250 mm diameter), suggesting that development is entirely lecithotrophic. The follicle cells that mediate connections between developing embryos and the maternal individual probably have a mechanical role only, providing support and possibly facilitating the accommodation of a large number of embryos to maximize the branchial space available for brooding. Fil: Ituarte, Cristian Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina